Eats, shoots & leaves why, commas really do make a difference - Truss(3, (BLynnes (New York Putnam's Sons, 2006)
See how using (or not using) a comma can change the meaning of a sentence
5 18
Keywords: English language -- Punctuation -- Juvenile literature; English language -- Punctuation